"Your feet call you”: Impact of an intervention to improve self-care of feet in diabetes - Bañuelos-Barrera, Patricia; Ochoa-Martínez, César; Domínguez-Chávez, Claudia Jennifer; Lara-Esqueda, Agustín; Ortiz-Rivas, Miriam Karina (Horizonte Sanitario, 2023)
Objective: To evaluate the impact of an individualized educational intervention on knowledge, self-care of the feet, glycemic control, risk of ulceration and incidence of ulcers in patients with type 2 diabetes. Material and Methods: The intervention study, carried out on 65 outpatients, over 35 years of age, with type 2 diabetes, were randomly distributed into two groups: the control group (35), who received a manual on foot care, and the intervention group (30), who received the intervention, a foot care kit, and manual. Follow-up was done at three and six months after the intervention. Statistical analysis included the Chi-square test, Wilcoxon test and the ANOVA test of repeated measures. Results: The intervention improved knowledge and foot self-care in the intervention group with significant differences between groups (p=.001), but not the glycemic control or the ulceration risk. Conclusions: The program "Your feet call you" was partially effective, and this study can be ordinarily replicated in first-level institutions to improve self-care and prevent foot ulceration in the medium term. Keywords: Diabetes mellitus; Type 2; Knowledge; Self-care; Foot; Intervention studies.